Verifying the effect of silanized nitinol surface: An in-vitro study. (November 2019) - Sinha, S; Begam, H; Nandi, S; Chanda, A
Abstract: Although Nitinol is a popular orthopedic implant material, there is still need of surface modification of nitinol to control nickel leaching. Main challenge with such surface modification of orthopedic implant is that along with cost effective modification the surface, there should be good integration with the surrounding bone tissue. In this study surface of the shape memory Nitinol was modified by simple silanization process using (3-aminopropyl)triethoxysaline(APTES). Here we report the interaction between the Nitinol surface (both bare and silanized) and the human osteoblastic cells (MG63cell) over a period of 48 hours. From detailed investigations, involving MTT assay and immunocytometry it was found that silanized Nitinol performed marginally better than bare Nitinol. The effect of silanization on surface composition and roughness of the specimen is also reported here to explain the superiority of silazised samples in case of cell-material interaction.